Improving the Ability to Read the Qur’an through the Tilawati Method among Students of SMA IT Pondok Pesantren Al Hidayah - M Rajani; A. Hariri Aikon Noor; Umi Rauhun; Muhammad Wahyudi; Juwita Juwita; Mubarak Mubarak (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This classroom action research aims to improve students’ ability in reading the Qur’an through the Tilawati method at SMA IT Pondok Pesantren Al Hidayah. The background of this study is the low level of students’ fluency, accuracy, and understanding of tajwid in Qur’anic recitation. Many students still experience difficulties in pronouncing makhraj, applying tajwid rules, and reading fluently. Therefore, an effective and systematic learning method is needed to enhance students’ Qur’anic reading skills, this research employed a classroom action research design consisting of planning, implementation, observation, and reflection in two cycles. The participants of this study were students of SMA IT Pondok Pesantren Al Hidayah. Data were collected through observation sheets, reading tests, and documentation. The Tilawati method was implemented through structured learning stages, including classical, individual, and talaqqi-based practices, supported by rhythmic recitation and teacher guidance. the results of the study showed that the implementation of the Tilawati method significantly improved students’ Qur’anic reading skills. Students demonstrated better fluency, accuracy in tajwid, and confidence in reading. The average score increased from the pre-cycle to the second cycle. In addition, students showed higher motivation and active participation during the learning process. Thus, the Tilawati method can be considered effective in improving students’ ability to read the Qur’an in Islamic boarding school environments.